2009
DOI: 10.1063/1.3273368
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric polymer/silver nanocomposites with high dielectric constant and high thermal conductivity

Abstract: Ferroelectric polymer nanocomposites with silver (Ag) nanoparticles as inclusions were prepared and the dielectric properties and thermal conductivity were studied. The results showed that the nanocomposites have high dielectric constant and high thermal conductivity. When the loading level of Ag nanoparticles is 20.0 vol %, the dielectric constant and thermal conductivity of the nanocomposites were 120 at 103 Hz and 6.5 W/mK, respectively. Our results also showed that there is no percolation in the nanocompos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
124
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 190 publications
(125 citation statements)
references
References 15 publications
1
124
0
Order By: Relevance
“…As expected, the k of all the RGO@SiO 2 /PDMS composites is largely decreased with an increase in frequency, suggesting a strong frequency dependence of k of all the composites. The strong dependence of k is ascribed to interfacial polarization effect (also named as the MaxwellWagner-Sillars (MWS) effect) of RGO@SiO 2 on PDMS molecules caused by the accumulation of many free charges at the internal interfaces between RGO@SiO 2 and PDMS [42]. Is has enough time to accumulate charge at the interfaces between RGO@SiO 2 and the rubber matrix at low frequency, resulting in the high k of the composites.…”
Section: Electromechanical Properties Of Go@sio 2 /Pdms Compositesmentioning
confidence: 99%
“…As expected, the k of all the RGO@SiO 2 /PDMS composites is largely decreased with an increase in frequency, suggesting a strong frequency dependence of k of all the composites. The strong dependence of k is ascribed to interfacial polarization effect (also named as the MaxwellWagner-Sillars (MWS) effect) of RGO@SiO 2 on PDMS molecules caused by the accumulation of many free charges at the internal interfaces between RGO@SiO 2 and PDMS [42]. Is has enough time to accumulate charge at the interfaces between RGO@SiO 2 and the rubber matrix at low frequency, resulting in the high k of the composites.…”
Section: Electromechanical Properties Of Go@sio 2 /Pdms Compositesmentioning
confidence: 99%
“…The λ value of the Al/PVDF composite with 60 vol% Al reached approximately 1.74 W/mK, nearly seven times than that of the original PVDF matrix. Huang et al [138] prepared a series of thermally conductive Ag/PVDF nanocomposites, and the obtained λ value of the Ag/PVDF nanocomposite with 20 vol% Ag was significantly improved to 6.5 W/mK. Yu et al [139] reported a novel method to fabricate Cu-plated polystyrene (Cu-p-PS) composites with Cu thin film networks, created by the Cu metallization of PS bead and the hot press molding of Cu-plated PS beads (Fig.…”
Section: Metal Fillersmentioning
confidence: 99%
“…As the thermal conductivity of epoxy systems is very low (about 0.2 W/(m!K)), thermally conductive fillers are added to these composites in order to dissipate the heat generated in electronic devices [6]. Various kinds of fillers, such as metals and metal oxides [7,8], aluminum nitride (AlN) [9][10][11], boron nitride (BN) [12], and silicon carbide (SiC) [13] have been applied to prepare thermally conductive polymer composites. Among them, AlN is a nontoxic, low cost substance, readily available as high purity powder.…”
Section: Introductionmentioning
confidence: 99%